(3GdfbGjIs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg hGdTcQ dg gPg fbGjg ef YOI Ydhe jMJGL GdWGdH EdjgG hjJhba cd Yde Ojfi YdjgG CUhd GdOjf Yde jLH ajg YeG jLH EYJbGOg s
(3BNQgG (B:s
(3haVd bhe GdJhcd Ydi GdEcJSGH hJaGhJ GdeQGJH dG QGO daVGFdg hdG eYbH dMceg hgh MSHi hfYe Gdhcjd cedJ HMeO Gddg JYGdi hMSf Yhfg hJhajbg hJSOjOg Hefg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3eNJUQ ai CQHYI YTQ YdekG eY RHOI eSGFdgGs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B_ (3GdQHGW (B(314 d) s
Keywords: (3GdeLGejYs